Psychosocial burden of healthcare professionals in times of COVID-19 – a survey conducted at the University Hospital Augsburg - Zerbini, Giulia; Ebigbo, Alanna; Reicherts, Philipp; Kunz, Miriam; Messman, Helmut (GMS German Medical Science, 2020)
Objective: The outbreak of COVID-19 was declared a pandemic by the WHO in March 2020. Studies from China, where the virus first spread, have reported increased psychological strain in healthcare professionals. The aim of this study was to investigate the psychosocial burden of physicians and nurses depending on their degree of contact with COVI9 patients. In addition, we explored which supportive resources they used and which supportive needs they experienced during the crisis.Methods: Data were collected between March and April 2020 at the University Hospital Augsburg. A total of 75 nurses and 35 physicians, working either in a special COVID-19 ward or in a regular ward, took part in the survey. The participants filled in two standardized questionnaires (the Patient Health Questionnaire, PHQ; and the Maslach Burnout Inventory, MBI), and reported their fear of a COVID-19 infection and stress at work on a 10-point Likert scale. Finally, they answered three open-ended questions about causes of burden, supportive resources and needs during the crisis.Results: Nurses working in the COVID-19 wards reported higher levels of stress, exhaustion, and depressive mood, as well as lower levels of work-related fulfilment compared to their colleagues in the regular wards. Physicians reported similar scores independent of their contact with COVID-19 patients. The most common causes for burden were job strain and uncertainty about the future. Psychosocial support as well as leisure time were listed as important resources, and a better infrastructure adjustment to COVID-19 at the hospital (e.g. sufficient staff, keeping teams and working schedules stable) as suggestion for improvement.Conclusions: Our findings indicate that especially nurses working in COVID-19 wards are affected psychologically by the consequences of the pandemic. This might be due to a higher workload and longer time in direct contact with COVID-19 patients, compared to physicians.